The Dizziness Handicap Inventory questionnaire scores before-and-after vestibular rehabilitation therapy of presbyastasis patients - Etty Sekardewi; Achmad Chusnu Romdhoni; Haris Mayagung Ekorini (Oto Rhino Laryngologica Indonesiana, 2020)
Background: Presbyastasis is multifactorial balance dysfunction that occurs in the elderly person. Presbyastasis can increase the risk of fall, anxiety, and decrease the quality of life. Vestibular rehabilitation therapy (VRT) has been proven effective to overcome balance disorders, and it is safe for the elderly. Several studies had reported the success of VRT for balance disorders. All this time, the accomplishment of VRT was assessed by using balance test, which had a risk of falling in elderly patients. Objective: To find out the outcome of Dizziness Handicap Inventory (DHI) questionnaire score in presbyastasis patients after VRT. Method: Ten presbyastasis patients in age range 60-75 years old who met the study criteria were taken by consecutive sampling. A longitudinal observational (pre and posttest) study by analyzing the DHI questionnaire scores. Assessment was performed twice, before and after VRT. The data was analyzed using paired T test and Wilcoxon signed rank test with outcome p<0.05. Result: The measurement of the emotional subscale DHI (DHI.E) showed the mean score before VRT was 4.00 (1.63), after therapy was 0.00 (0.63), p=0.004. The functional subscale (DHI.F) measurement showed the mean score before VRT was 10.40 (3.98), after therapy was 2.40 (2.07), p 0.00. The mean score of physical subscales (DHI.P) measurement before VRT was 9.00 (4.40), after therapy was 2.00 (1.58), p=0.008. The total DHI score (DHI.T) before VRT was 22.6 (7.67), after VRT was 4.20 (2.2) with p=0.000. Conclusion: There was an improvement in DHI questionnaire score before and after 6 weeks VRT.Keywords: Vestibular rehabilitation therapy (VRT), Dizziness Handicap Inventory (DHI), presbyastasis ABSTRAK Latar belakang: Presbiastasis dapat meningkatkan angka jatuh, kecemasan dan menurunkan kemandirian sehingga menurunkan kualitas hidup pada usia lanjut. Terapi rehabilitasi vestibuler (TRV) merupakan modal terapi yang terbukti dapat mengatasi gangguan keseimbangan, dan aman untuk usia lanjut. Beberapa penelitian melaporkan adanya keberhasilan TRV pada penderita gangguan keseimbangan. Keberhasilan dari TRV selama ini dinilai dengan menggunakan pemeriksaan keseimbangan yang memiliki risiko jatuh pada penderita usia lanjut. Tujuan: Membuktikan adanya perubahan skor kuesioner Dizziness Handicap Inventory (DHI) pada penderita presbiastasis sesudah TRV. Metode: Sepuluh penderita presbiastasis usia 60-75 tahun yang memenuhi kriteria penelitian diambil secara consecutive sampling. Studi observasi longitudinal (pre dan posttest) dengan menghitung dan menganalisis skor kuesioner DHI. Pengukuran dilakukan 2 kali yaitu sebelum TRV dan sesudah TRV. Analisis data dilakukan dengan paired T test dan Wilcoxon signed rank test, dengan hasil p<0,05. Hasil: Pengukuran skor kuesioner DHI subskala Emotional (DHI.E) sebelum TRV mempunyai mean 4,00 (1,63), 6 minggu sesudah TRV didapatkan mean 0,00 (0,63), p=0,004. Hasil subskala Functional (DHI.F) sebelum TRV didapatkan mean 10,40 (3,98), 6 minggu sesudah TRV, mean 2,40 (2,07), p=0,00. Pada subskala Physical (DHI.P) didapatkan mean 9,00 (4,40), dan 6 minggu sesudah TRV didapatkan mean 22,6 (7,67), sesudah TRV didapatkan mean 4,20 (2,2) dengan p=0,000. Kesimpulan: Terdapat perbaikan skor kuesioner DHI sesudah 6 minggu terapi rehabilitasi vestibuler (TRV).